Biogeographic patterns, assembly processes, and functional potential of root-associated microbiomes across the native range of the endangered orchid Changnienia amoena - Zhu, Wenhao; Quan, Zhanghua; Wang, Ren; Liu, Xingjian; Zhou, Jiayu (Frontiers in Microbiology, 2026)
IntroductionChangnienia amoena is an endangered orchid endemic to China, with notable medicinal and ornamental significance. Like other orchids, it relies heavily on microbial symbionts for germination, growth, and survival; however, its associated microbiomes remain poorly understood.MethodsThis study employed high-throughput amplicon sequencing targeting bacterial 16S rRNA and fungal ITS regions and provided an in-depth characterization of the root-associated microbiomes of C. amoena across its native range.ResultsBoth bacterial and fungal communities exhibited significant biogeographic patterns, but only fungal Shannon-Wiener diversity showed a decreasing trend with increasing latitude. The neutral model revealed predominantly stochastic assembly of bacterial communities. In contrast, fungal communities exhibited a lower estimated migration rate, indicating a relatively stronger influence of non-neutral processes on their assembly. Soil nutrients emerged as key environmental drivers shaping microbial communities. Functional predictions highlighted multiple bacterial functions related to nitrogen cycling and the enrichment of mycorrhizal fungi, suggesting the functional potential of root-associated microbes in promoting plant nutrient acquisition, growth, and environmental adaptation. Co-occurrence network analysis further revealed positive associations between mycorrhizal fungi and potentially beneficial bacteria based on taxonomic inference.DiscussionThis study reveals distinct biogeographic patterns, assembly processes, and functional potentials of root-associated microbiomes of C. amoena, which not only expands the understanding of the plant–soil-microbe interactions, but also provides crucial insights for manipulating them for the conservation of this endangered orchid.